Mechanical Properties And In-Vitro Corrosion Behaviour Of Mg-6zn-Bioactive Glass Composite - Wong, Kae Yuan (Universiti Sains Malaysia, 2017)
Biodegradable magnesium and its alloys are widely used as potential orthopedic bone implant materials due to their good biocompatibility in the bio-environment. To improve the mechanical properties and in-vitro corrosion behaviour of biodegradable magnesium, magnesium-zinc matrix reinforced with different weight percentage (0, 5, 10, 15 wt.%) of bioglass (45S5) were fabricated using powder metallurgy technique in this research work. The composites were compacted under pressure 300 MPa and were sintered at 350°C. Microstructure of composites was observed using an optical microscope. Density was determined using a gas pycnometer. The mechanical properties such as microhardness and compressive strength were studied. Corrosion rate was investigated by immersion test. Density (1.845 - 1.958 g/cm3) of sintered composites are close to the density value of natural bone (1.8 - 2.1 g/cm3). All composites show improvement in microhardness and compressive strength if compared to the naked Mg-6Zn alloy. Mg-6Zn/5BG shows the highest microhardness value (67.21 HV) and compressive strength (169MPa). Agglomeration of bioglass particles has been seen on the microstructure of composites with 10 wt.% and 15 wt.% of bioglass content. In-vitro corrosion test shows that Mg-6Zn/5BG has the lowest corrosion rate which is 0.154 mm/year. However, composites that have porosity of more than 7.0% (Mg-6Zn/10BG and Mg-6Zn/15BG) will have adverse effect on corrosion resistance. The addition of bioglass to the Mg-6Zn has also improved the formation of apatite layer after soaking in SBF solution.